An Analysis of Teacher’s Perceptions and Challenges in Implementing the Merdeka Curriculum for Teaching English Reading Skills at SMA Negeri 1 Gowa - Ririn Asta Rina; Ratu Yulianti Natsir; Sujariati Sujariati (PT ARRUS Intelektual Indonesia, 2024)
This research aimed to find out the perceptions and challenges faced by teachers in the implementation of the Merdeka Curriculum in teaching reading skills. This study used a quantitative descriptive method with data obtained from questionnaires and interviews with three grades of X English teachers at SMA Negeri 1 Gowa. The results of the study showed that teachers had a positive perception of the importance of learning to read, with an average score of 84.33% obtained by respondents. This positive perception was obtained based on the results of the questionnaire, the teachers stated that they agreed with the statements that showed that they understood the importance of learning to read, motivate students, use interesting learning strategies and others. While the teachers' challenges were obtained from the results of the interviews, the challenges faced by teachers include difficulties in integrating technology and difficulties in increasing students' interest in reading. The results of this study are expected to provide insight into the application of the Independent Curriculum in teaching reading.